2020
DOI: 10.1172/jci129012
|View full text |Cite
|
Sign up to set email alerts
|

The Mir181ab1 cluster promotes KRAS-driven oncogenesis and progression in lung and pancreas

Abstract: Study approval. All experiments in mice were performed according to the MD Anderson Cancer Center Institutional Animal Care and Use Committee (IACUC, protocol 00001636), UCSF Committee on Animal Care (APLAC), and the University of Navarra Ethical Committee on Animal Research (CEEA, protocol 068-13). Regarding human data, only normalized/processed data of coded clinical information were made available to this study to preserve patients' anonymity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 82 publications
1
21
0
Order By: Relevance
“…Also, a prominent KRAS signature has been linked to the activation of several important transcription factors, including GATA3 29 . Overexpression of GATA3 was seen in KRAS mutant lung cancer cells and further up‐regulated the tumorigenesis through miRNAs 30 …”
Section: Discussionmentioning
confidence: 99%
“…Also, a prominent KRAS signature has been linked to the activation of several important transcription factors, including GATA3 29 . Overexpression of GATA3 was seen in KRAS mutant lung cancer cells and further up‐regulated the tumorigenesis through miRNAs 30 …”
Section: Discussionmentioning
confidence: 99%
“…27 Massive research showed the important effects of miRNAs during the development of multiple cancers. 28,29 In triple-negative breast cancer, miR-551b-3p can activate the OSM signaling pathway, thus inhibiting the occurrence and development of tumors. 30 In CSCC, the expression patterns of mir-205 and mir-203 showed a typical negative correlation, which could be used as prognostic markers.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the relevance of miR-181a in PDAC initiation, it was shown that miR-181ab1 cluster tunes this process in Ptf1aCre/+, KrasLSLG12D/+ Trp53fl/fl, and Mir181ab1−/− mice [ 25 ]. Mir181ab1 knock-out developed less PanIN lesions, and it had less aggressive pancreatic tumours than controls.…”
Section: Discussionmentioning
confidence: 99%